Guidelines for immunization of children following multisystem inflammatory syndrome in children - Ludwikowska, Kamila; Okarska-Napierała, Magdalena; Matkowska-Kocjan, Agnieszka; Jackowska, Teresa; Wysocki, Jacek; Kuchar, Ernest; Peregud-Pogorzelski, Jarosław; Szenborn, Leszek (Pediatria Polska - Polish Journal of Paediatrics, 2022)
Multisystem inflammatory syndrome in children (MIS-C) is a late complication of SARS-CoV-2 infection, either symptomatic or asymptomatic. The underlying cause is immunological dysregulation, leading to severe inflammatory processes. Children with MIS-C require hospital treatment, the use of immunomodulating drugs, and often intensive care. COVID-19 vaccination is safe and highly effective in preventing not only severe COVID-19, but also MIS-C in adolescents. However, there are no explicit vaccination recommendations for children who underwent MIS-C. We present a summary of current knowledge on vaccinations against COVID-19 in the context of MIS-C. Moreover, we propose guidance concerning vaccinations for children following MIS-C.